Liberalización, política monetaria y dolarización: La la experiencia ecuatoriana - Pitarque , Juan Carlos (2020)
I want to share with you the Ecuadorian experience in the liberalization of its financial services, the financial crisis that we experienced between 1998 and 1999, the decision to dollarize the economy, and the monetary policy instruments that still have a central bank in dollarization.